2016
DOI: 10.1002/sce.21215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanistic Reasoning: Toward Bridging the Gap Between the Molecular and Cellular Levels in Life Science Education

Abstract: ABSTRACT:Although learning about DNA, RNA, and proteins is part of the upper secondary biology curriculum in most countries, many studies report that students fail to connect molecular knowledge to phenomena at the higher level of cells, organs, and organisms. As a result, many students use memorization and rote learning as a coping strategy when presented with molecular-level concepts. This study explores the potential of a new educational approach that aims at facilitating students to interpret animations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 38 publications
3
71
0
1
Order By: Relevance
“…cell biology [9][10][11][12][13][14][15][16] genetics [17][18][19][20][21] physiology [7,[22][23][24][25][26][27]] ecology [7,28,29] evolution [30][31][32] Based on known learning difficulties in genetics, Knippels [19] suggests the Yo-Yo learning and teaching strategy. It incorporates the idea to make the levels of organisation explicit and to think to and from the levels over the course of several lessons.…”
Section: Biological Topic Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…cell biology [9][10][11][12][13][14][15][16] genetics [17][18][19][20][21] physiology [7,[22][23][24][25][26][27]] ecology [7,28,29] evolution [30][31][32] Based on known learning difficulties in genetics, Knippels [19] suggests the Yo-Yo learning and teaching strategy. It incorporates the idea to make the levels of organisation explicit and to think to and from the levels over the course of several lessons.…”
Section: Biological Topic Publicationsmentioning
confidence: 99%
“…Knippels and Waarlo [51] found few descriptions of challenges. Only one of the articles Knippels and Waarlo [51] reviewed offers insights into challenges: Van Mil et al [14] reported that their teaching approach was difficult for teachers.…”
Section: Research Question 4: How Do the Authors Describe The Challenmentioning
confidence: 99%
“…Several earlier designs for learning science with a complex systems perspective usually implemented the computational ABM approach, which encourages causal reasoning and leads to an understanding of the mechanisms underlying the phenomena (Levy & Wilensky, 2008). Such designs have demonstrated important advantages to learning through a complexity approach (in chemistry: Holbert & Wilensky, 2014;Levy & Wilensky, 2009b;Stieff & Wilensky, 2003;Wilensky, 2003;in physics: Brady, Holbert, Soylu, Novak, & Wilensky, 2015;Sengupta & Wilensky, 2009;in biology: Dickes et al, 2016;van Mil, Boerwinkel, & Waarlo, 2013;Van Mil, Postma, Boerwinkel, Klaassen, & Waarlo, 2016;Wilensky & Reisman, 2006;Wilkerson-Jerde, Wagh, & Wilensky, 2015; in materials science: Blikstein & Wilensky, 2009;in robotics: Levy & Mioduser, 2010). For example, in biology education, van Mil et al (2013) suggested including measures for the development of molecular mechanistic reasoning to improve students' understanding of cell behavior as a complex system in which cellular processes emerge from molecular interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They claimed that a teacher can build on a student's intuitive reasoning about mechanisms. In a later paper, van Mil et al (2016) demonstrated a way to do this by using a strategy based on students' interpretation of animations of (sub)cellular processes as models of molecular mechanisms. Conversely, Stieff (2011) found that learning high school chemistry through a complexity approach was no better than a normative approach for conceptual learning (although the complexity approach group improved in representational competence).…”
Section: Literature Reviewmentioning
confidence: 99%
“…in other science domains, consisted of addressing student problems in understanding the cellular and molecular mechanisms of disease, and focused on molecular mechanistic reasoning (van Mil et al, 2016), examining teachers' challenges when discussing ethical dilemmas in genetics (van der Zande et al, 2012), and finding international consensus on which genetic knowledge is required by scientifically literate citizens (Boerwinkel, Yarden and Waarlo, 2017).…”
Section: Empowering Students To Cope With Scientific Innovations: Lesmentioning
confidence: 99%